The Agricultural Potentiality Of Some Wetland Soils Under Sylhet Basin Of Bangladesh (Dhaka University Journal of Biological Sciences, 2012)
An investigation was conducted to study some representative wetland soils under Sylhet basin of Bangladesh with a view to evaluating the agricultural potentiality and its management options. The soils are nutritionally very productive. Soil textural and other environmental conditions are more appropriate for rice production. The contents of nitrogen and boron is low. Probably, the denitrification process leads to the loss of nitrogen in this basin soils. Other nutrients seem to be at a balanced condition for the successful growth of deep water rice. Boro and deep water T. Aman were introduced in the study area in recent times. Availability of irrigation water in the dry periods and shallow inundation level in the monsoon may be the main cause of such cropping pattern. Due to the changes in landuse, demand for nitrogen and phophorus fertilizer have increased. pH value stands near neutral which indicates the agricultural viability of the soils. The present investigations ascertained that the study area including the wetland of Bangladesh can be economically exploited through appropriate nutrient management without any extra agro?chemical use. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9743 DUJBS 2012 21(1): 39-46